Does IQ influence association between working memory and adhd symptoms in young adults? - Soares, Pedro San Martin (2022)
Objective: This study examined the association between WM and ADHD symptoms in young adults and whether IQ-score influenced this association. Method: Data from the 1993 Pelotas (Brazil) Birth Cohort Study were analyzed (N = 2,845). Working memory and ADHD symptoms were collected at 22 years. IQ was examined at age 18. Poisson regression with robust variance was used to assess the associations between working memory and ADHD symptoms. We also evaluated whether IQ modified associations between working memory and ADHD symptoms. Results: Working memory was negatively associated with Inattention symptoms of ADHD. The association between working memory and hyperactivity-impulsivity symptoms of ADHD varied by IQ. Conclusions: This study provides new insights to theories about the relationship between WM and ADHD symptoms as well as the development of interventions aimed at improving the performance of WM in ADHD.